2019
DOI: 10.7717/peerj.6529
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Simao pine in China revealed by SRAP markers

Abstract: Background Simao pine (Pinus kesiya Royle ex Gordon var. langbianensis (A. Chev.) Gaussen) is one of the most important tree species in the production of timber and resin in China. However, the genetic diversity of the natural populations has not been assessed to date. In this study, sequence related amplified polymorphism (SRAP) markers were used to investigate the genetic composition of natural Simao pine populations. Method The SRAP mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…In addition to molecular markers, allozyme markers are normally also one of the important method for genetic diversity studying though the result were different for E. breviaristatus populations from similar eco-region [18]. As dominant markers, SRAP markers could reveal higher genetic polymorphism in E. breviaristatus than with allozyme markers (PPB = 92.37% for SRAP markers and PPB = 57.1% for allozyme markers, Table S6), which showed that the SRAP markers had more effectiveness than allozyme in analyzing genetic diversity, which was also proved by Wang et al [42].…”
Section: Genetic Diversity At Species and Population Levelsmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to molecular markers, allozyme markers are normally also one of the important method for genetic diversity studying though the result were different for E. breviaristatus populations from similar eco-region [18]. As dominant markers, SRAP markers could reveal higher genetic polymorphism in E. breviaristatus than with allozyme markers (PPB = 92.37% for SRAP markers and PPB = 57.1% for allozyme markers, Table S6), which showed that the SRAP markers had more effectiveness than allozyme in analyzing genetic diversity, which was also proved by Wang et al [42].…”
Section: Genetic Diversity At Species and Population Levelsmentioning
confidence: 56%
“…And it is very clear that the three remaining populations were extremely different from each other. Gene flow is essential for understanding the evolution of plants and the population processes within and among species [42]. Even if there was subtle genetic structure, its function may be weakened by foreign immigrants [43].…”
Section: Population Genetic Structurementioning
confidence: 99%
“…Fresh and young healthy needles from parents and mapping population (100 hybrid individuals) were collected and frozen in liquid nitrogen at once. The genomic DNA was isolated using the improved cetyl trimethyl ammonium bromide (CTAB) method [ 53 ]. The permission of the plant materials collection was approved by Southwest Forestry University (project number: 2018Y31).…”
Section: Methodsmentioning
confidence: 99%
“…Fresh and young healthy needles from parents and mapping population (100 hybrid individuals) were collected and frozen in liquid nitrogen at once. The genomic DNA was isolated using the improved cetyl trimethyl ammonium bromide (CTAB) method (Wang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%